Factibilidad agronómica y entomológica de la siembra intercalada caña de azúcar (Saccharum officinarum L.) y fríjol (Phaseolus vulgaris L.). - Mantilla G, C.E.; Raigosa Bedoya, J. de D.; Zúñiga V, H. (Universidad Nacional de Colombia, 2018)
Fríjol-Phaseolus vulgaris